In Vitro Assessment of Synthetic Nano Engineered Graft Designed for Further Clinical Study in Nerve Regeneration - Ali Sadeghi; Fatholah Moztarzadeh; Jamshid Aghazadeh Mohandesi; Claudia Grothe; Kirsten Haastert Talini; Ali Reza Zalli; Reza Jalili Khoshnoud (International Clinical Neuroscience Journal, 2018)
Background: Electrospun nanofibrous scaffolds are considered as promising candidates in neural tissue regeneration due to their ability to support neural cell attachment, spreading and proliferation. Methods: In this paper, various type of nanofibers scaffold based on polycaprolactone) (PCL) were fabricated using electrospinning. The main drawback of PCL scaffolds is their low bioactivity of scaffold surface. To overcome this surface and composition modification was used to enhanced hydrophilicity and bioactivity of scaffold. Results: The scanning electron microscopy (SEM) results indicate that fiber diameter entirely depends on the solvent system and added component of gelatin and chitosan which by adding gelatin and chitosan fiber diameter decreased. In vitro studies using PC12 cells revealed that the plasma surface modified and blended scaffold with chitosan and gelatin nanofibrous scaffold supports cell attachment, spreading and indicate a significant increase in proliferation of PC12 in the presence of chitosan. The results demonstrated that gelatin and chitosan caused a significant enhancement in the bioactivity of the scaffold, which confirmed by MTT assay and improved the cell spreading and proliferation of neural cell on the scaffolds. Conclusion: Based on the experimental results, the PCL/chitosan/PPy conductive substrate could be used as a potential scaffold for clinical research in the field of neural regeneration and healing.